4‐2: Distinguished Student Paper: High Efficiency Color‐Converted Micro‐LED Displays. Issue 1 (29th May 2019) - Gou, Fangwang; Hsiang, En-Lin; Tan, Guanjun; Lan, Yi-Fen; Tsai, Cheng-Yeh; Wu, Shin-Tson
Abstract : With funnel‐tube array, the optical efficiency of the color‐converted micro‐LED display is improved by 3X, while the crosstalk is eliminated. After optimization of the taper angle, the ambient contrast ratio is also improved due to higher light intensity.